Assessment of prognostic scores in brain metastases from breast cancer. Issue 3 (4th December 2013) - Tabouret, Emeline; Metellus, Philippe; Gonçalves, Anthony; Esterni, Benjamin; Charaffe-Jauffret, Emmanuelle; Viens, Patrice; Tallet, Agnés
Abstract: Background: Breast cancer (BC) is the second most common cause of brain metastases (BM). Optimal management of BM from BC is still debated. In an attempt to provide appropriate treatment and to assist with optimal patient selection, several specific prognostic classifications for BM from BC have been established. We evaluated the prognostic value and validity of the 6 proposed scoring systems in an independent population of BC patients with BM. Methods: We retrospectively reviewed all consecutive BC patients referred to our institution for newly diagnosed BM between October 1995 and July 2011 ( n = 149). Each of the 6 scores proposed for BM from BC (Sperduto, Niwinska, Park, Nieder, Le Scodan, and Claude) was applied to this population. The discriminative ability of each score was assessed using the Brier score and the C-index. Individual prognostic values of clinical and histological factors were analyzed using uni- and multivariate analyses. Results: Median overall survival was 15.1 months (95% CI, 11.5–18.7). Sperduto-GPA ( P < .001), Nieder ( P < .001), Park ( P < .001), Claude ( P < .001), Niwinska ( P < .001), and Le Scodan ( P = .034) scores all showed significant prognostic value. The Nieder score showed the best discriminative ability (C-index, 0.672; Brier score error reduction, 16.1%). Conclusion: The majority of prognostic scores were relevant for patients with BM from BC in our independent population, and the Nieder score seems to present the best predictive value but showed a relatively low positive predictive value. Thus, these results remain insufficient and challenge the routine use of these scoring systems.